2004
DOI: 10.1111/j.1399-0012.2004.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term study on hyperlipidemia in stable renal transplant recipients

Abstract: Renal transplantation is associated with a characteristic pattern of dyslipidemia, with increased TC, LDL and HDL, and a decrease in TG. Patients with pre-existing hypercholesterolemia were at higher risk for post-transplant hypercholesterolemia. Although the incidence of hypercholesterolemia peaks within the first year after transplantation, this remains a long-term complication in a significant proportion of patients on low dose immunosuppressive medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
2
16
0
2
Order By: Relevance
“…These results show that patients with hyperlipidemia identified before transplantation had fewer hyperlipidemia diagnoses after transplantation than did those with NOHL post-transplantation. These incidence rates suggested by the claims data are somewhat lower than those observed by Tse et al in single center studies [13]. While NOHL is less prevalent among wait-listed patients, we found a non-zero hyperlipidemia incidence rate pre-transplant, consistent with Tse et al [13].…”
Section: Cohort Characteristics and Incidencesupporting
confidence: 60%
“…These results show that patients with hyperlipidemia identified before transplantation had fewer hyperlipidemia diagnoses after transplantation than did those with NOHL post-transplantation. These incidence rates suggested by the claims data are somewhat lower than those observed by Tse et al in single center studies [13]. While NOHL is less prevalent among wait-listed patients, we found a non-zero hyperlipidemia incidence rate pre-transplant, consistent with Tse et al [13].…”
Section: Cohort Characteristics and Incidencesupporting
confidence: 60%
“…3,4,19 Findings are also consistent with studies done by Tse KC, et al in, Kimak E, et al in and Salahi H, et al in. [20][21][22] This study has shown an association of use of diuretics with increased lipid levels at 6 and 12 months. Association of diuretics with elevation in lipid levels has also been shown by the study done by Ames RP and Hill P in 1976.…”
Section: Discussionmentioning
confidence: 99%
“…The associated dyslipidemia plays an important part in the pathogenesis of cardiovascular disease in this population [113]. Dyslipidemia in transplant recipients is largely due to the use of immunosuppressive agents, particularly prednisone, cyclosporine, and sirolimus, which are commonly used in this population to prevent graft rejection.…”
Section: Effect Of Kidney Transplantation On Lipid Profilementioning
confidence: 99%